Oxygen signalling in metabolic regulation: short, intermediate, and long term roles - Hochachka, P.W. (Acta Andina, 2025)
We are led at least tentatively to conclude from this analysis that O2 sensing and signal transduction pathways are critically involved. (i) in the regulation of acute changes in ATP turnover rates in response to increasing or decreasing oxygen availability (or to change in work and perfusion rates), (ii) in the regulation of intermediate term responses to hypoxia (such as EPO biosynthesis, cfos and cjun activation, or suppression of gluconeogenic pathway enzymes). (iii) in the regulation of longer term responses to moderate hypoxia (for example, up regulation of tissue mitochondrial volume densities, of oxygen carrying capacitites, or of oxygen efficient metabolic pathways), and (iv) in the regulation of long term responses to extreme hypoxia (for example, down regulation of tissue mitochondrial volume densities, adjustments in anaerobic/aerobic metabolic capacities, or adjustments in oxygen efficiency of metabolic pathways). Perhaps even more evident than the above is the conclusion that oxygen sensing, signal transduction, and expression pathways in metabolic adjustments to hypoxia are still largely unexplored, especially in the comparative field. Although current models for coupling O2 sensing to regulation of ATP turnover are still a long way from being complete or confirmed, they are, in principle, useful and attractive for several reasons: (i)they can account for the often observed relationship between VO2 and perfusion, (ii) they develop a mechanistic basis for O2 conformity (VO2 varying with [O2] or with O2 delivery) over broad concentrations ranges usually very much higher than the Km for O2 for mitochondrial metabolism, (iii) they supply a mechanism for coordinate and near instantaneous regulation, upwards, of all components in ATPase and ATP synthesis pathways with change in O2 availability, (iv) they supply a mechanistic explanation for up or down regulation of ATP turnover rate with mínimal change in concentrations of intermediates in pathways of ATP utilization or of ATP production, and (v) they display interesting potential for strategic transfer to clinical situations, because they seem to be generally applicable to most tissues. Whereas for such obvious reasons these models may be useful, it is not yet clear whether or not they will turn out to be correct For this further research is clearly required.